Simulation of MPPT with a PMSG-based wind energy conversion system considering variable wind speed - Abogrean , Elbahlul; Elhatmi , Eddawi Ali; Saad , Jamila Alnouri (Scientific Journal of University of Benghazi, 2022)
The proposed method provides a good tracking performance through detecting the variation in the wind speed rapidly. In addition, the implementation does not require prior information on the wind turbine parameters, air density, or wind speed. By investigating the change directions of the mechanical output power of the wind turbine and the rotor speed of the generator, the proposed MPPT algorithm can determine an optimal speed to achieve the maximum power point (MPP). Then, this optimal speed is set to the reference in the speed control loop to force the system to operate at the MPP. The DC-DC boost converter has been used to boost up the low AC voltage generated by the PMSG directly driven by the wind turbine. The mechanical output power of the wind turbine is calculated from the mechanical torque which is measured directly by sensor. The proposed scheme is modeled and simulated under SIMULINK/MATLAB. The simulation results are accurate and validate the wind energy conversion system.